BELAJAR MANDIRI MELALUI SYSTEM OF RICE INTENSIFICATION (SRI) DI DUABELAS SUBAK DI PROVINSI BALI - Adi Putra, I Gede Setiawan (dwijenAGRO, 2011)
The traditional irrigation water management system in Bali known as Subak has a great potential for adopting the SRI innovation. In the adoption process, there is also a learning process on the individual members of the subak. The objectives of this research are (1) to analyze the characteristics of the Subak members, competence of facilitators, competence of Subak caretakers, the perceptions, and attitudes that influence Subak members in Self Directed Learning, and (2) to formulate the strategy of approach and effective extention in improving Self Directed Learning of the Subak members. This research was carried out in seven regencies in the province of Bali. The total amount of samples in this research is 104 farmers selected through the Stratified Random Sampling methods which also included famers that applied SRI innovations. Primary data were collected through interviews and direct obserations from September to October 2011. The design of this research is an ex Post Facto and data analyzed using Structural Equation Model (SEM). The result of this research shows that: (1) The better the perceptions, attitudes towards SRI, characteristics of members of Subak, competence of facilitators and caretakers of the Subak, the better the level of Self Directed Learning of Subak members; and (2) The role of  facilitator is very important to helping subak  members decided to accept an agricultural innovation. The discovery of dominant factors which affect the adoption of SRI among Subak members will facilitate the caretakers in making a change in Bali. Keywords: adoption, innovation, SRI, farmers, caretakers